Amphibian and reptile biodiversity in the semi-arid region of the municipality of Nopala de Villagrán, Hidalgo, Mexico - Andrea J. Roth-Monzón; Andrés Alberto Mendoza-Hernández; Oscar Flores-Villela (PeerJ, 2018)
Current global changes are putting both biodiversity and the processes that depend on it at risk. This is especially true for semi-arid regions and the flagship groups that inhabit them, such as amphibians and reptiles. Semi-arid regions are often thought to have lower biodiversity and thus have been overlooked, resulting in the underestimation of their biological richness. Therefore, the aim of this study was to conduct an inventory of amphibians and reptiles in the semi-arid municipality of Nopala de Villagrán, Mexico, and analyze its biodiversity in relation to the seasons, vegetation and microhabitat. During a year of fieldwork, we found 24 species in the area, most of them of low abundance, and one of which was recorded for the first time for the state of Hidalgo. We documented five amphibian species and 19 reptile species. We also found that observed species richness was higher in the rainy season and in xeric scrub vegetation, although only the season differences were significant according to rarefaction curves. Our findings highlight the importance of seasonality and vegetation type for the species that inhabit this semi-arid region. This study broadens our understanding of the importance of semi-arid regions and, by extension, that of other areas with similar characteristics.